Low-Interference Dual Resonant Antenna Configurations for Multistandard Multifunction Handsets and Portable Computers - Mohamed Sanad; Noha Hassan (International Journal of Antennas and Propagation)
Low-interference dual resonant antenna configurations are developed for multistandard multifunction mobile handsets and portable computers. Only two wideband resonant antennas can cover most of the important wireless applications in portable communication equipment. The frequency bands of the dual antenna configuration can be adjusted according to the wireless applications that are required to be covered. The bandwidth that can be covered by each antenna is about 80% without using matching or tuning circuits. Three sample dual antenna configurations with different frequency bands are presented. The interference between the low-band and high-band antennas of these three configurations is investigated, and the ways of reducing this interference are studied. The most effective factor on the interference between the low-band and high-band antennas is their relative orientations. When the low-band and high-band antennas of each configuration are perpendicular to each other, the isolation between them significantly increases. This eliminates the need for any special tools or techniques to suppress the mutual coupling between them. The new antennas have very small cross-sectional areas, and they are made of a flexible material. They do not require any additional components or ground planes. They can be used as internal, external, or partially internal and partially external antennas.